PENGARUH GOOD CORPORATE GOVERNANCE DAN VOLUNTARY DISCLOSURE TERHADAP BIAYA HUTANG (COST OF DEBT) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Akhmad Samhudi (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
This research aims to examines variables influencing cost of debt in banking companies listed in Indonesian Stock Exchange. Independent variables are Good Corporate Governance (independent commissioner, managerial ownership, institutional ownership, and audit quality) and voluntary disclosure.There are 19 banking companies which taken as samples during period 2013 to 2015. Analysis method in this research is multiple regression analysis which used SPSS program 16.0 version. Simultaneously testing used F-test and partially testing used t-test.The result shows that partially, independent variables which significantly influencing cost of debt are audit quality and voluntary disclosure with each significant value 0.003 and 0.049 (less than 0.05). Simultaneously, independent commissioner, managerial ownership, institutional ownership, audit quality and voluntary disclosure significantly influencing cost of debt in banking companies listed in Indonesia Stock Exchange with significant value 0.000 (below from 0.05). Adjusted R2 value 0,305 shows that 30,5% variation of companies cost of debt can be explained by independent commissioner, managerial ownership, institutional ownership, audit quality and voluntary disclosure and the explained by variables which not used in this research. Keywords: Good Corporate Governance, Voluntary Disclosure, Cost of Debt